Implementing capnography to help improve patient safety during procedural sedation: quality improvement in a high-volume gastroenterology department. Issue Volume 33:Issue S1(2021) (19th April 2021) - Bisschops, Raf; Saunders, Rhodri; Dooms, Christophe; Hoffman, Ilse; van der Merwe, Schalk; Weissbrod, Rachel; Torres, Rafael Torrejon; Van Assche, Gert; Demedts, Ingrid
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Respiratory compromise is a major cause of adverse events during procedural sedation; continuous monitoring is vital for identifying and halting decompensation. We performed a quality improvement investigation to assess patient safety during procedural sedation in gastroenterology and the impact of implementing capnography monitoring. Patients and methods: Sedation-related adverse events and interventions were prospectively recorded during the endoscopic procedure and in recovery. Assuming rates in published literature, power analysis determined that at least 1332 patients were required to show a 20% improvement in patient safety. Recorded sedation-related adverse events (mild and severe oxygen desaturations, bradycardia and tachycardia) and interventions were anonymized and aggregated to evaluate the quality improvement. Patient safety under current care was determined before capnography (Medtronic) was implemented in combination with training. Results: Between February 2018 and April 2018, a baseline (1092 patients) for outcomes under current care was completed, with 11.45 events per 100 procedures recorded. Between May 2018 and July 2018, 1044 procedures including capnography monitoring were performed with 5.08 events per 100 procedures recorded. The distribution of American Society of Anesthesiologists scores and procedure types between baseline and capnography were comparable. The absolute difference between baseline and capnography was −6.4 events per 100 procedures [95% confidence interval (CI), −4.1 to −8.7; P  ≤ 0.0001]. The 55% reduction in adverse events surpassed the 20% improvement in patient safety set as the goal of this quality improvement. After multivariate regression, the adjusted odds ratio for events after implementation of capnography was 0.46 (95% CI, 0.32–0.66). Conclusions: Addition of capnography to current care significantly decreased procedure-related safety events.